Pengaturan Tata Ruang Wilayah Terhadap Alih Fungsi Lahan Pertanian Menjadi Objek Wisata di Bali - Komang Ajus Nada Putra; I Nyoman Gede Sugiartha; Luh Putu Suryani (Jurnal Analogi Hukum, 2025)
The regulation of spatial planning regarding the conversion of agricultural land into tourist attractions in Bali is analyzed through a scientific approach, examining its impacts on the environment, economy, and local community's social aspects. The research focuses on policies, regulations, and spatial planning implementations influencing land transformation. In this context, the problem formulation revolves around (1) how spatial planning regulates the conversion from agricultural land to tourist areas in Bali?, and (2) how its legal implications on spatial planning due to such transformation. This study adopts a normative law approach, indicating that the regulation of spatial planning concerning the conversion of agricultural land into tourist areas in Bali is outlined in the Provincial Regulation of Bali Number 2 of 2023 regarding the Spatial Planning Plan of Bali Province for the Year 2023-2024. The legal impacts of the transformation of agricultural land into tourist areas in Bali will depend on the regulations in force in Bali.